PERAN KINERJA KEUANGAN DAN GOOD CORPORATE GOVERNANCE PADA PENGUNGKAPAN SUSTAINABILITY REPORT - Sitanggang, Daniel Ortega; Paramitadewi, SettingsHyasshinta Dyah Sweztika Lukitaning (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2022)
This study aims to analyze financial performance and good corporate governance's role in sustainability reports. The method used in this research is descriptive analysis method and multiple linear analysis, and the data is processed through Statistical Package for the Social Sciences (SPSS) version 23. This study shows that financial performance positively affect sustainability reports. Meanwhile, good corporate governance proxies with committee audit positively influence sustainability reports compared to the independent commissioner.